PENGARUH LATIHAN SERVIS DIBAWAH TALI TERHADAP HASIL AKURASI SHORT BACKHAND SERVICE DALAM PERMAINAN BULUTANGKIS PADA CLUB PB. JUNIOR KEC.TUALANG KAB. SIAK SRI INDRAPURA - Topan, Ali Topan; Wijayanti, Ni Putu Nita Wijayanti Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract, this study was conducted to determine whether there was an effect of exercise service under the rope to the accuracy of the results of short backhand service in badminton game on club PB. Junior excl. Wanderer Kab. Siak Sri Indrapura, so that an athlete is able to perform short service properly and can direct short service at the desired target. The shape of this research is the experimental treatment (Experimental), the population in this study were athletes PB. Junior excl. Wanderer Kab.Siak Sri Indrapura.sample in this study is the athletes PB. Junior beginners aged 15 years and amounted to 10 athletes. The sampling technique that is non-random sampling (non-random). Non-random sampling is a sampling process that is not based on randomization. In this study researchers used a purposive sampling technique. Purposive sampling is a sampling of the researcher pointed directly who will be sampled in the study, but pemilihanya based on the specific objectives of the research conducted. Researchers consider the suitability of a problem with the selected individuals. The instruments used in this research is testing the accuracy of short service, which aims to measure the accuracy of short service backhand. After that, the data is processed with statistics, to test the normality of the test at a significant level 0,05α lilifors. The hypothesis is contained service under the rope exercise influence on the Result Accuracy short backhand service. Based on t test analysis produces Ttabel Thitung of 4.87 and 1.833, meaning Thitung> Ttabel. Based on statistical data analysis, there are on average Pree-test of 47.7 and an average post-test of 50.4, and based on t test after the calculated difference increased numbers or ride with an average that is 2.7. From the description above it can be concluded there is a service under the rope exercise influence on the results Accuracy Short backhand service in badminton game on club PB. Junior district.Wanderer Kab.Siak Sri Indrapura. Keywords: Exercise Services under the rope, Accuracy Results Short Backhand Service